HOW TO BE A DIPLOMAT - Westcott, Nicholas (ROUTLEDGE, 2026)
With the international system entering a period of extreme flux, diplomacy has never been more important, and how to do it successfully more relevant. This book considers what diplomacy is, its purpose, rules, structures, how it is done, what it involves, the skills required, the impact of technological and societal changes, and how diplomats ensure success. In short, it is about handling people and problems, particularly in other countries, without coming to blows. Drawing on the author's extensive personal experience, this readable volume focuses on the practical problems diplomats regularly face, such as negotiating an agreement, working with a hostile government, dealing with dual nationals imprisoned for political reasons, looking after local staff, engaging with civil society, responding to humanitarian crises, and what to do if a war breaks out on your doorstep. This is an invaluable training resource for anyone working at the coal face of international relations and a guide to how to navigate, operate, behave, negotiate, and survive diplomatic life. Such diplomatic skills will be of wider relevance in many walks of life - international, commercial, bureaucratic, even family.